Heavy metal changes related to land use changes in a karst area: a case study in Changshun, Guizhou Province, China - Jiang, Xin; Wang, Xingfu; Liu, Yi; Huang, Yu; Huang, Xianfei (Frontiers in Environmental Science, 2024)
Karst environments are characterized by fragile ecological systems, and environmental pollution has increased the living pressure of people in these regions. This research aimed to study the pollution status of heavy metals (Pb, Cd, Hg, As and Cu) in soils from different land uses in Changshun County, a karst area in southwestern China. Soil samples were collected from natural forest lands (NFL), natural brush lands (NBL), natural pasture lands (NPL), artificial forestlands (AFL), artificial brush lands (ABL) and artificial pasture lands (APL). The results suggested that the soil profile characteristics of studied heavy metals varied significantly among different land uses.Concentrations of the studied heavy metals in all soil samples collected from the NFL were lower than those in samples from the other land uses. Forest trees can protect soils from heavy metal pollution caused by atmospheric deposition; this is especially true for Hg. In cultivated forestlands and brush lands, special attention should be paid on soil Cd pollution which may be caused by utilization of fertilizer. Changing both the natural and artificial pasture lands to forestlands may benefit the local ecosystem since Hg contamination.